2011
DOI: 10.1262/jrd.11-049k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antioxidant Supplementation on Duodenal Se-Met Absorption in Ethanol-exposed Rat Offspring In Vivo

Abstract: Abstract. The nutritional deficiencies provoked by ethanol consumption, during gestation or lactation, can contribute to multiple birth defects in offspring. In order to improve our knowledge about selenium (Se) distribution in pups exposed to ethanol, the present study evaluated the effect of this drug on intestinal development and determined its action on duodenal absorption of selenomethionine (Se-Met). To determinate if supplementation could improve Se absorption and its serum values, we used two antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…It could be concluded that dietary Se supplementation to dams mitigated the adverse effects of alcohol in ethanol-exposed offspring (Ojeda et al 2009a;Ojeda et al 2010a;Nogales et al 2011), increasing the expression of GPx1, GPx4 and SelP P (Jotty et al 2013), thus confirming Se therapy as an exogenous supplementation with a real antioxidant capacity and biological D r a f t function, being especially important after ethanol consumption and during gestation and breastfeeding -the early stages of pups' lives.…”
Section: R a F Tmentioning
confidence: 87%
See 2 more Smart Citations
“…It could be concluded that dietary Se supplementation to dams mitigated the adverse effects of alcohol in ethanol-exposed offspring (Ojeda et al 2009a;Ojeda et al 2010a;Nogales et al 2011), increasing the expression of GPx1, GPx4 and SelP P (Jotty et al 2013), thus confirming Se therapy as an exogenous supplementation with a real antioxidant capacity and biological D r a f t function, being especially important after ethanol consumption and during gestation and breastfeeding -the early stages of pups' lives.…”
Section: R a F Tmentioning
confidence: 87%
“…Despite this corporal redistribution of maternal Se deposits, milk Se levels were lower in ethanol-exposed dams (Jotty et al 2013). Moreover, weaning pups intake less milk and ethanol alters their intestinal absorption decreasing the pups' intestinal perimeter, as well as its length and weight (Nogales et al 2011, Bhalla et al 2004, even affecting the Se-methionine D r a f t transport system. Finally, at the end of lactation, the surviving pups presented a high retardation in their development together with a deficient Se intake.…”
Section: Pre-and Postnatal Alcohol Exposure: Effects On Selenium Balamentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, to worsen the relationship among EtOH exposure and Se homeostasis, EtOH-exposed weaning pups intake less milk and have lower intestinal perimeters, presenting a down-regulation in the SelMet transport system [ 157 , 158 ]. This lead to a greater Se homeostasis disruption, more than in dams [ 159 ], which mainly compromised Se deposits in liver, kidney and heart.…”
Section: Oxidative Stress-programming Pathologies and Sementioning
confidence: 99%
“…In order to reinforce the hypothesis that EtOH-exposure during preconception, gestation and lactation periods affects the oxidative profile and Se homeostasis in the progeny, which is in part related to their metabolic future health, in our laboratory, dietary Se antioxidant supplementation (0.5 ppm of sodium selenite) was given to EtOH–exposed Wistar dams. With this model, we pursued different objectives: to analyze the reproductive parameters and the intestinal SelMet absorption process in weaning pups [ 158 ], to evaluate Se retention and body distribution in dams and their offspring [ 155 , 159 , 184 ], to improve fetal and lactating pups hepatic oxidative balance, in part related to gestational and breastfeeding parameters [ 7 , 154 , 160 , 166 ], and to study selenoprotein liver expression and their possible biological role in weaning pups [ 156 ]. The narrow window between therapeutic and toxic doses of Se, as well as the dependence of its effect on the applied form, dose and method of treatment, makes the choice of an effective supplement a very complex issue.…”
Section: Oxidative Stress-programming Pathologies and Sementioning
confidence: 99%